The Effect of the Benson Relaxation Technique on Insomnia Levels in the Elderly - Vincencius Surani; Lilik Pranata; Sri Indaryati; Keristina Ajul (Formosa Journal of Science and Technology, 2023)
A common problem that often occurs in the elderly is sleep disturbance which can affect quality of life. One of the most common sleep disorders is insomnia. This study aims to analyze the impact of the benson relaxation technique on the level of insomnia in the lederly. This research is a quantitative study with a one group pretest-postest (pre-experimental study) design. The number of samples in this tudy were 30 respondents with a sampling technique using total sampling. The data collection tool used a questionnaire consisting of a survey of respondent characteristics and an insomnia rating scale. The intervension used is the benson relaxation technique. Data collection was carried out before and after the implementation of the intervention. Research data were analyzed using the wilcoxon signed-rank test with a p-value <0.05. The conclusion in this study is that there is a significant difference in the level of insomnia in the elderly between before and after the implementation of the intervention.